2022
DOI: 10.3389/fgene.2022.989646
|View full text |Cite
|
Sign up to set email alerts
|

Signature of seven cuproptosis-related lncRNAs as a novel biomarker to predict prognosis and therapeutic response in cervical cancer

Abstract: Background: Given the high incidence and high mortality of cervical cancer (CC) among women in developing countries, identifying reliable biomarkers for the prediction of prognosis and therapeutic response is crucial. We constructed a prognostic signature of cuproptosis-related long non-coding RNAs (lncRNAs) as a reference for individualized clinical treatment.Methods: A total of seven cuproptosis-related lncRNAs closely related to the prognosis of patients with CC were identified and used to construct a progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Numerous studies have highlighted the contributions of cuproptosis-related genes to uncontrolled tumor growth. Dihydrolipoamide Branched Chain Transacylase E2 (DBT), a key enzyme in transforming α-keto acid into acyl-CoA, served as a protective factor in cervical cancer [ 53 ]. FOXD2-AS1 and LINC02154 are the risk factors for KIRC patients [ 48 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the contributions of cuproptosis-related genes to uncontrolled tumor growth. Dihydrolipoamide Branched Chain Transacylase E2 (DBT), a key enzyme in transforming α-keto acid into acyl-CoA, served as a protective factor in cervical cancer [ 53 ]. FOXD2-AS1 and LINC02154 are the risk factors for KIRC patients [ 48 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, 18 cuproptosis-related lncRNAs associated with CC prognosis were identified by univariate Cox regression, and after LASSO and multivariate Cox regression, a risk prediction model containing AL441992.1, SOX21-AS1, AC011468.3, AC012306.2, FZD4-DT, AP001922.5, RUSC1-AS1, and AP001453.2 was constructed. There have been several previous reports on the establishment of cuproptosis-related lncRNA models for predicting the prognosis of cervical cancer 37 39 (Table 2 ). Compared to a study by Liu, Wang et al using only the TCGA database, we added the GEO database (GSE44001) as an external validation to make the obtained results more persuasive.…”
Section: Discussionmentioning
confidence: 99%
“…26 Despite the progress made in the treatment of cervical cancer, due to the heterogeneity of tumors, there are significant differences in prognosis even among patients with similar clinical characteristics, which indicates that the existing classification and clinicopathological characteristics are insufficient to predict the prognosis of patients. 27 As cervical cancer is a highly preventable tumor, there is a great need for more effective biomarkers to more accurately determine which treatments patients will benefit most from. 28 Lactate has long been considered a metabolic waste product, but recent studies have found that lactate tightly links two fundamental hallmarks of cancer: immune evasion and metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%